Intra-Testicular Signals Regulate Germ Cell Progression and Production of Qualitatively Mature Spermatozoa in Vertebrates - Meccariello, Rosaria; Chianese, Rosanna; Chioccarelli, Teresa; Ciaramella, Vincenza; Fasano, Silvia; Pierantoni, Riccardo; Cobellis, Gilda (Frontiers in Endocrinology, 2014)
Spermatogenesis, a highly conserved process in vertebrates, is mainly under the hypothalamic-pituitary control, being regulated by the secretion of pituitary gonadotropins, FSH and LH, in response to stimulation exerted by Gonadotropin Releasing Hormone (GnRH) from hypothalamic neurons. At testicular level, gonadotropins bind specific receptors located on the somatic cells regulating the production of steroids and factors necessary to ensure a correct spermatogenesis. Indeed, besides the endocrine route, a complex network of cell-to-cell communications regulates germ cell progression, and a combination of endocrine and intragonadal signals sustains the production of high quality mature spermatozoa. In this review we focus on the recent advances in the area of the intragonadal signals supporting sperm development.